The function is (-x+3)/ (3x-2) and we get f(1)=1 and differentiation is f'(x)=-7/ (9x²- 12x+4).
Given that,
The function is (-x+3)/ (3x-2)
We have to find f(1) and f'(x).
Take the function expression
f(x)= (-x+3)/ (3x-2)
Taking x as 1 value
f(1)= (-1+3)/(3(1)-2)
f(1)=2/1
f(1)=1
Now, to get f'(x)
With regard to x, we must differentiate.
f(x) is in u/v
We know
u/v=(vu'-uv')/ v² (formula)
f'(x)= ((3x-2)(-1)- (-x+3)(3))/ (3x-2)²
f'(x)= ((-3x+2)-(-3x+9))/ 9x²- 12x+4
f'(x)=(-3x+2+3x-9)/ 9x²- 12x+4
f'(x)=2-9/ (9x²- 12x+4)
f'(x)=-7/ (9x²- 12x+4)
Therefore, The function is (-x+3)/ (3x-2) and we get f(1)=1 and differentiation is f'(x)=-7/ (9x²- 12x+4).
To learn more about function visit: brainly.com/question/14002287
#SPJ1
Answer:
If your question is -2 - 4 - 2 - 2.1 then the answer is -10.1
Step-by-step explanation:
-2 - 4 - 2 - 2.1
= (-2 - 4 ) - 2 - 2.1 Combine -2 with -4 or subtract them
= -6 - 2 - 2.1
= (-6 - 2 )- 2.1 Combine -6 and -2
= -8 -2.1 Combine -8 and -2.1
= -10.1
<h3><u><em>
Please rate this and please give brainliest. Thanks!!!
</em></u></h3><h3><u><em>
Appreciate it! : )
</em></u></h3><h3><u><em>
And always,
</em></u></h3><h3><u><em>
SIMPLIFY BANANAS : )</em></u></h3>
Answer:
Tip Total: $ 11
Total (Bill + Tip): $ 62
Step-by-step explanation:
Answer: B
Step-by-step explanation: